Artificial intelligence with Python : your complete guide to building intelligent apps using Python 3.x and TensorFlow 2 /: your complete guide to building intelligent apps using Python 3.x and TensorFlow 2. ([2020]) - Artasanchez, Alberto; Joshi, Prateek
No abstract available